Determination of critical velocity in arm strokes, leg kicks and whole crawl strokes for competitive swimmers and water polo players - Ogasawara, K.; Shimada, K.; Tachi, M.; Wakayoshi, K. (Japanese Journal of Sciences in Swimming and Water Exercise, 2009)
The purpose of this study were to determine the endurance performances for swimming in whole crawl strokes (Swim), arm strokes (Pull) and leg kicks (Kick) using critical swimming velocity (CV), and to compare these parameters between water polo players (skilled and unskilled) and competitive swimmers (short and long distance). The results showed strong and significant linear relationships between swimming distance and the time in all subjects. Calculated CV of Swim, Pull and Kick were lower in the water polo players than in the competitive swimmers. Also, the relationships between the CV of Pull or Kick and Swim were different between the water polo players and the competitive swimmers. These results demonstrated that, as well as for Swim, CV can also be used to determine the endurance performances for Pull and Kick. However, the relationships between the endurance performances for Pull, Kick and Swim were indicated to be different between water polo players and competitive swimmers.